Sick and stuck at home – how poor health increases electricity consumption and reduces opportunities for environmentally-friendly travel in the United Kingdom. (October 2018) - Büchs, Milena; Bahaj, AbuBakr; Blunden, Luke; Bourikas, Leonidas; Falkingham, Jane; James, Patrick; Kamanda, Mamusu; Wu, Yue
Abstract: Research on the determinants of direct and indirect energy use has identified a range of relevant socio-economic factors. However, we still know little about possible influences of people's health on their energy use. Do people in poor health use less energy because they are on lower incomes, or do they have additional domestic energy needs as they spend more time at home? Does poor health reduce mobility for all or just some (environmentally-friendly) modes of travel? This paper examines these questions through analysis of the representative UK Understanding Society survey. We find that poor health is generally linked to lower home energy use and lower engagement in all forms of travel. However, once we control for income and other socio-demographic factors, poor health is related to higher electricity consumption. These findings have important policy implications as it means that people in poor health would be additionally burdened by higher cost of electricity but, due to their low mobility, less so by higher cost of energy-intensive forms of travel. While promoting good health could support environmentally-friendly travel, additional measures would be required to prevent a rise of energy-intensive modes of travel.